In silico design of angiotensin-converting enzyme 2 (ACE2) recombinant protein to block the S1 protein pathway of COVID-19 virus - Yaser Ghazi (Open Journal of Proteomics and Genomics - Peertechz Publications, 2020)
Coronavirus is a large family of viruses that includes the common cold and the SARS virus. The Chinese corona, or coronavirus, is a new respiratory virus that began in late 2019 and early 2020 in the province of Hubby and Wuhan, China, and became known as COVID-19. The COVID-19 virus genome is a positive single-stranded RNA (ssRNA (+)) and is 29903 nucleotides long, encoding twelve different proteins. One of these proteins is called the S-protein. During the S-protein contamination cycle, it is divided into two subunits, S1 and S2. The subunit S1, which contains the Receptor Binding Protein (RBD), binds directly to the protease domain of the Angiotensin-Converting Enzyme 2 (ACE2) protein and enters the cell through it. In this study first the ACE2 protein sequence extracted from the NCBI site. To convert the protein to an extracellular protein and excrete it out of the cell, the signal peptide sequence was added to the beginning of the recombinant protein and two amino acids, cysteine and asparagine, added to both sides of the signal peptide sequence to create a self-catalyzing process similar to that found in Inteins. The identifiable motif was then incompletely added to both sides of the peptide signal sequence by ACE2 sequences with F-H-L amino acids sequence. Also, amino acids involved in direct interaction between the two subunits of ACE2 protein were inhibited. Dimerization was removed from the amino acid sequence, eventually to improve the lamb The interaction between the two ACE2 proteins designed with the S1 protein virus enhanced the physicochemical properties of the protein designed using the PROTPARAM and GPMAW sites..